Therapeutic Potential of Mitotic Kinases' Inhibitors in Cancers of the Gastrointestinal System - Aadil Javed; Gianluca Malagraba; Mahdieh Yarmohammadi; Catalina M. Perelló-Reus; Carles Barceló; Teresa Rubio-Tomás (MDPI AG, 2022)
Mitosis entails mechanistic changes required for maintaining the genomic integrity in all dividing cells. The process is intricate and temporally and spatially regulated by the ordered series of activation and de-activation of protein kinases. The mitotic kinases ensure the stepwise progression of entry into mitosis after the G2 phase of the cell cycle, followed by prophase, pro-metaphase, metaphase, anaphase, telophase, and subsequently cytokinesis and birth of two daughter cells with equal segregation and distribution of the genome. The major mitotic kinases include cyclin-dependent kinase 1 (CDK1), Aurora A and B Kinases, and Polo-Like-Kinase 1 (PLK1), among others. Overexpression of some of these kinases has been reported in many cancers as the mitotic fidelity and genome integrity are interlinked and dependent on these regulators, the native irregularities in these factors can be targeted as therapeutic strategies for various cancers. Here, we report and summarize the recent updates on the literature describing the various mitotic inhibitors targeting kinases, which can be used as potential therapeutic interventions for gastrointestinal cancers including gastric cancer, liver cancer, pancreatic cancer and colorectal cancer.